Preparation method of TiO2 / MIL-101 (Cr) photocatalyst

By growing TiO2 in situ on MIL-101 (Cr), the TiO2/MIL-101 (Cr) photocatalyst with Type II heterojunction structure is solved, and the photocatalytic hydrogen production performance is significantly improved.

CN119524929APending Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411646288.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Photogenerated electron holes in single MOFs-based photocatalytic materials are easy to recombinate, limiting their photocatalytic efficiency.

Method used

The TiO2/MIL-101 (Cr) photocatalyst was prepared by ultrasonic synthesis of MIL-101 (Cr) and solution thermal method to synthesize TiO2 prepolymer solution, and then reacted under high temperature and high pressure to form a Type II heterojunction structure.

Benefits of technology

By forming the Type II heterojunction structure, the electron and energy band structures in the composite material are optimized, photogenerated carrier separation and transmission are promoted, and the photocatalytic hydrogen production performance is significantly improved. The hydrogen production performance of 23% TiO2/MIL-101(Cr) is 2.6 times that of the pure phase MIL-101(Cr).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524929A_ABST
    Figure CN119524929A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a TiO2 / MIL-101 (Cr) photocatalyst, belongs to the technical field of photocatalysts, and aims to prepare a series of TiO2 / MIL-101 (Cr) heterojunctions for photocatalytic hydrogen production through in-situ growth of TiO2 nanoparticles on the MIL-101 (Cr) surface by a hydrothermal method. By adopting the preparation method of the TiO2 / MIL-101 (Cr) photocatalyst with the structure, the photocatalytic hydrogen production performance is improved, the excellent hydrogen production performance is attributed to a TypeII heterostructure formed by TiO2 and MIL-101 (Cr), electron and energy band structures in a composite material are optimized, and separation and transmission of photon-generated carriers are promoted, so that the catalytic activity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to a method for preparing a TiO2 / MIL-101 (Cr) photocatalyst. Background Art

[0002] With the rapid development of economy, the demand and consumption of energy are increasing. Meanwhile, environmental pollution is becoming increasingly serious. The development of renewable and clean energy is urgent. Hydrogen energy is considered as one of the environmentally friendly and sustainable alternatives to fossil fuels because of its renewable, clean and efficient characteristics. Therefore, the use of solar energy to produce hydrogen has great significance and development potential. Inorganic semiconductors, such as titanium dioxide and cadmium sulfide, have been widely used in photocatalytic hydrogen production, but their insufficient structure and easy recombination of carriers still restrict their development.

[0003] Metal-organic frameworks (MOFs) are porous crystalline materials self-assembled from metal ions or clusters and organic ligands. They have the characteristics of easy structural modification, adjustable pore size, high specific surface area, and abundant active sites. Their organic ligands can be used as antennas to capture sunlight, and the metal center can be used as an active center to achieve water decomposition and hydrogen production. However, the photogenerated electrons and holes in single MOFs-based photocatalytic materials are still easy to recombine, which limits their photocatalytic efficiency.

[0004] Heterojunctions can effectively improve photocatalytic efficiency, which is mainly attributed to the carrier migration at the heterojunction interface, which minimizes charge recombination and results in separated electrons and holes at the reduction and oxidation sites, respectively. For example, Wu et al. synthesized a Zr-MOF / g-C3N4 Z-type heterojunction, which inhibited the recombination of photogenerated carriers to a certain extent and improved the photocatalytic hydrogen production activity. Therefore, it is very necessary to prepare a more efficient heterojunction. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a TiO2 / MIL-101 (Cr) photocatalyst to solve the problem that photogenerated electron holes in the current single MOFs-based photocatalytic material are still easy to recombine, which limits its photocatalytic efficiency.

[0006] To achieve the above object, the present invention provides a method for preparing a TiO2 / MIL-101 (Cr) photocatalyst, comprising the following steps:

[0007] Step 1, synthesis of MIL-101(Cr):

[0008] Terephthalic acid and chromium (III) nitrate nonahydrate were added to a reaction kettle, 14 mL of water and 0.1 mL of HF were added, and ultrasonication was performed for 20 min to obtain a uniform solution. The mixture was transferred into a polytetrafluoroethylene-lined reaction kettle for reaction. After the reaction was completed, the mixture was naturally cooled to room temperature, and the precipitate was collected by centrifugation and washed with DMF and ethanol several times, and dried in vacuum at 60°C to obtain MIL-101 (Cr);

[0009] Step 2, synthesis of TiO2 precursor solution:

[0010] Add concentrated nitric acid to ethanol and add tetrabutyl titanate, stir to prepare TiO2 precursor solution, and use it immediately after preparation;

[0011] Step 3, preparation of x% TiO2 / MIL-101(Cr):

[0012] 30 mL of TiO2 precursor solution and 40 mg of MIL-101(Cr) were added to 20 mL of ethanol, and 0.3 mL of water was added. The mixture was stirred at room temperature for 30 min, and then the mixed solution was transferred to a high temperature and high pressure reactor for reaction. The solid obtained by centrifugation was washed three times with ethanol and then dried under vacuum conditions at 60°C to obtain a green powder, named x% TiO2 / MIL-101(Cr).

[0013] Preferably, in the above-mentioned method for preparing a TiO2 / MIL-101(Cr) photocatalyst, in the step 1, 0.333 g of terephthalic acid and 0.800 g of chromium (III) nitrate nonahydrate are used to prepare MIL-101(Cr).

[0014] Preferably, in the above-mentioned method for preparing a TiO2 / MIL-101(Cr) photocatalyst, the reaction conditions in the polytetrafluoroethylene-lined reactor in step 1 are high temperature and high pressure at 220°C for 8 hours.

[0015] Preferably, in the above method for preparing a TiO2 / MIL-101(Cr) photocatalyst, in step 3, 140 μL of concentrated nitric acid is added to 120 mL of ethanol, and 200 μL of tetrabutyl titanate is added.

[0016] Preferably, in the above-mentioned method for preparing a TiO2 / MIL-101(Cr) photocatalyst, the mixing and stirring time in the step 2 is 2 minutes, and the TiO2 precursor solution is prepared and used immediately.

[0017] Preferably, in the above-mentioned method for preparing a TiO2 / MIL-101(Cr) photocatalyst, the reaction conditions of the high temperature and high pressure reactor in step 3 are heating at 120°C for 24 hours.

[0018] Preferably, in the above-mentioned method for preparing a TiO2 / MIL-101(Cr) photocatalyst, the TiO2 / MIL-101(Cr) photocatalyst prepared by the above-mentioned method is used to achieve efficient photocatalytic hydrogen production.

[0019] Therefore, the present invention adopts a method for preparing a TiO2 / MIL-101(Cr) photocatalyst of the above structure, and TiO2 has the advantages of good chemical stability, non-toxicity, low cost and easy availability. MIL-101(Cr) has the advantages of good thermal stability, chemical stability and high specific surface area. The prepared TiO2 / MIL-101(Cr) improves the photocatalytic hydrogen production performance, among which 23% TiO2 / MIL-101(Cr) has the best photocatalytic hydrogen production performance, which is 2.6 times that of pure phase MIL-101(Cr). Its excellent hydrogen production performance is attributed to the Type II heterostructure formed by TiO2 and MIL-101(Cr), which optimizes the electronic and energy band structure in the composite material, promotes the separation and transmission of photogenerated carriers, and thus improves the catalytic activity. It is proved by measurement that 23% TiO2 / MIL-101(Cr) has the best photogenerated carrier separation ability, and realizes efficient photocatalytic hydrogen production in kinetics.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns (a), FT-IR spectra (b), N2 adsorption isotherms (c) and Raman spectra (d) of MIL-101(Cr), TiO2 and x% TiO2 / MIL-101(Cr) in an embodiment of a method for preparing a TiO2 / MIL-101(Cr) photocatalyst of the present invention;

[0022] Figure 2 SEM images (ac), TEM images (d), HRTEM images (ef) of 23% TiO2 / MIL-101(Cr) of a method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to an embodiment of the present invention, and HAADF-STEM mapping (gi) of C, Cr and Ti;

[0023] Figure 3UV-Vis DRS spectra of MIL-101(Cr) and 23% TiO2 / MIL-101(Cr) in an embodiment of a method for preparing a TiO2 / MIL-101(Cr) photocatalyst of the present invention (a) and the corresponding Tauc spectra (b); Mott-Schottky curves of MIL-101(Cr) and titanium dioxide at 500, 1000 and 1500 Hz (cd); XPS spectra of 23% TiO2 / MIL-101(Cr), Cr 2p (f) and Ti 2p (eg); band gap information and the proposed charge transfer mechanism (h);

[0024] Figure 4 A TiO2Tauc diagram of an embodiment of a method for preparing a TiO2 / MIL-101 (Cr) photocatalyst according to the present invention;

[0025] Figure 5 The Tauc plot (x=13, 42, 37, 42, 47) of x% TiO2 / MIL-101(Cr) of a preparation method of a TiO2 / MIL-101(Cr) photocatalyst according to the present invention;

[0026] Figure 6 The TPC response and Solid PL spectra of MIL-101(Cr) and 23% TiO2 / MIL-101(Cr) of the embodiment of the preparation method of TiO2 / MIL-101(Cr) photocatalyst of the present invention (ab); EIS of x% TiO2 / MIL-101(Cr) (x=13, 23, 37, 42, 47) (c); Hydrogen production from MIL-101(Cr) and x% TiO2 / MIL-101(Cr) (x=13, 23, 37, 42, 47), conditions: acetonitrile 22.75mL, TEOA 1.25mL, full spectrum of 300WXe lamp (de); Cyclic test of more than 23% TiO2 / MIL-101(Cr) (f);

[0027] Figure 7 The TPC response (x=13, 437, 42, 47) of x% TiO2 / MIL-101(Cr) of a method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to an embodiment of the present invention;

[0028] Figure 8 This is the solid PL spectrum (x=13, 37, 42, 47) of x% TiO2 / MIL-101(Cr) in an embodiment of a method for preparing a TiO2 / MIL-101(Cr) photocatalyst of the present invention. DETAILED DESCRIPTION

[0029] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0031] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0032] The present application provides a method for preparing a TiO2 / MIL-101 (Cr) photocatalyst, comprising the following steps:

[0033] Step 1, synthesis of MIL-101(Cr):

[0034] 0.333 g of terephthalic acid and 0.800 g of chromium (III) nitrate nonahydrate were added to a reaction kettle, 14 mL of water and 0.1 mL of HF were added, and ultrasonic treatment was performed for 20 min to obtain a uniform solution. The mixture was transferred to a polytetrafluoroethylene-lined reaction kettle, and the reaction was carried out at 220° C. under high temperature and high pressure for 8 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the precipitate was collected by centrifugation, washed with DMF and ethanol several times, and dried in a vacuum at 60° C. to obtain MIL-101 (Cr);

[0035] Step 2, synthesis of TiO2 precursor solution:

[0036] Add 140 μL of concentrated nitric acid to 120 mL of ethanol, and add 200 μL of tetrabutyl titanate, stir for 2 min to prepare a TiO2 precursor solution, which is ready for use.

[0037] Step 3, preparation of x% TiO2 / MIL-101(Cr):

[0038] 30 mL of TiO2 precursor solution and 40 mg of MIL-101 (Cr) were added to 20 mL of ethanol, and 0.3 mL of water was added. The mixture was stirred at room temperature for 30 min, and then the mixed solution was transferred to a high temperature and high pressure reactor and heated at 120°C for 24 h. The solid obtained by centrifugation was washed three times with ethanol and then dried under vacuum conditions at 60°C to obtain a green powder, named x% TiO2 / MIL-101 (Cr).

[0039] The above method was used to in-situ grow TiO2 on MIL-101(Cr) to obtain x% TiO2 / MIL-101(Cr) (x=13, 23, 37, 42, 47) with different TiO2 contents, as shown in Table 1 below.

[0040] Table 1 Amounts of MOF and corresponding TiO2 precursors used to synthesize x% TiO2 / MIL-101(Cr)

[0041] sample <![CDATA[mL of TiO2 prepolymer]]> MIL-101(Cr) / mg <![CDATA[13%TiO2 / MIL-101(Cr)]]> 15.0 40 <![CDATA[23%TiO2 / MIL-101(Cr)]]> 30.0 40 <![CDATA[37%TiO2 / MIL-101(Cr)]]> 30.0 20 <![CDATA[42%TiO2 / MIL-101(Cr)]]> 37.5 20 <![CDATA[47%TiO2 / MIL-101(Cr)]]> 45.0 20

[0042] The crystal structure of photocatalytic materials was studied by PXRD, such as Figure 1 (a). The diffraction peaks of MIL-101(Cr) are consistent with the fitting values, indicating that MIL-101(Cr) was successfully prepared. At the same time, the characteristic peaks of the synthesized TiO2 at 24.8°, 37.2°, and 47.2° indicate that it is an anatase structure. After the solvothermal reaction of MIL-101(Cr) and the Ti precursor, the characteristic peaks of MIL-101(Cr) and anatase TiO2 can be observed at the same time, indicating that the synthesized material contains both MIL-101(Cr) and anatase TiO2.

[0043] At the same time, the structure of MIL-101(Cr) is maintained after the introduction of anatase TiO2. Figure 1 As shown in (bc), Fourier transform infrared spectroscopy (FT-IR) and Raman spectroscopy further indicate that the structure of MIL-101(Cr) is maintained after the introduction of anatase TiO2. Figure 1 (b) 1615 and 1397 cm -1 The infrared absorption peaks at 1017 and 732 cm are attributed to the asymmetric and symmetric stretching vibrations of the OCO of the H2BDC group. -1 The peak is attributed to CH of the benzene ring, 579 cm -1 The peak at belongs to Cr-O. Figure 1 As shown in (c), the Raman vibration bands of MIL-101(Cr) are located at 1609, 1458, 1150, and 867 cm -1 , corresponding to aromatic groups and carboxylic acid functional groups. It is worth noting that the wavelength range is 200-640cm-1 The peak in the range is attributed to the titanium oxygen bond of TiO2, and its peak intensity increases with the increase of TiO2 content, while the existence of titanium oxygen bond cannot be detected in pure MIL-101(Cr).

[0044] Further study of the specific surface area and pore structure of the photocatalyst, such as Figure 1 (d) As shown in Table 2, N2 adsorption-desorption isotherms were analyzed for TiO2, MIL-101(Cr) and x% TiO2 / MIL-101(Cr).

[0045] Table 2 BET surface area, pore volume and pore size of MIL-101(Cr) and x%TiO2 / MIL-101(Cr)

[0046] sample <![CDATA[BET surface area (m 2 g -1 )]]> <![CDATA[Pore volume (cm 3 g -1 )]]> Pore ​​size (nm) <![CDATA[TiO2]]> 76 0.33 17.52 MIL-101(Cr) 2836 1.45 2.04 <![CDATA[13%TiO2 / MIL-101(Cr)]]> 2630 1.35 2.05 <![CDATA[23%TiO2 / MIL-101(Cr)]]> 2560 1.28 2.01 <![CDATA[37%TiO2 / MIL-101(Cr)]]> 1462 0.82 2.30 <![CDATA[42%TiO2 / MIL-101(Cr)]]> 974 0.56 2.30 <![CDATA[47%TiO2 / MIL-101(Cr)]]> 880 0.44 2.01

[0047] TiO2 has 76m 2 / g BET specific surface area and 0.33cm 3 g -1 Compared with TiO2, MIL-101(Cr) has a larger specific surface area and pore volume, reaching 2836cm 3 / g and 1.45cm 3 g -1 Although the specific surface area and pore volume of the composite material decreased after the introduction of TiO2, the rich porous structure was still maintained. The 47% TiO2 / MIL-101(Cr) material with the smallest specific surface area still had a pore volume of 880 cm 3 / g and 0.44cm 3 g -1 At the same time, compared with MIL-101(Cr), the pore size of x%TiO2 / MIL-101(Cr) is basically unchanged, indicating that TiO2 may be loaded on the surface of MOF.

[0048] The morphology of the material and the distribution of TiO2 on the surface of the MOF material were observed by scanning electron microscopy. Figure 2 As shown, MIL-101(Cr) has a smooth surface and uniform octahedral morphology. After loading TiO2, 23%TiO2 / MIL-101(Cr) still maintains the original octahedral morphology, further indicating that the structure of MIL-101(Cr) is maintained, which is consistent with PXRD, FT-IR and Raman. It is worth noting that the surface of 23%TiO2 / MIL-101(Cr) is also relatively smooth, indicating that the synthesized TiO2 particles are very small.

[0049] 23% TiO2 / MIL-101(Cr) was further characterized by TEM, HRTEM and HAADF-STEM. From the TEM images, some black particles can be observed attached to the surface or inside of MOF, such as Figure 2 (d) HRTEM further observed that the lattice spacing of the fine black particles was 0.26nm, corresponding to the (200) plane of anatase TiO2, as shown in Figure 2 (ef) As shown. Through HAADF-STEM mapping, it was observed that C and Cr elements were evenly distributed inside the octahedron, while Ti element was mainly distributed on the surface of the octahedron, which further indicated that the synthesized fine TiO2 was mainly distributed on the surface of MIL-101(Cr), as shown in Figure 2 (gi) shown.

[0050] The light absorption of TiO2, MIL-101(Cr) and x%TiO2 / MIL-101(Cr) was studied by UV-vis DRS. Figure 3 (a) shows that the absorption edge of TiO2 is about 400nm. Compared with TiO2, MIL-101(Cr) and x%TiO2 / MIL-101(Cr) have a wider absorption range.

[0051] The Kubelka-Munk function calculation shows that the band gap of TiO2 is 3.31 eV. Figure 4 shown.

[0052] MIL-101(Cr) and 23%TiO2 / MIL101(Cr) have similar band gaps, 2.35eV and 2.32eV, respectively. The band gaps of several other x%TiO2 / MIL101(Cr) (x=13, 37, 42, 47) are as follows: Figure 5 .

[0053] The conduction bands of MIL-101(Cr) and TiO2 can be obtained through the Mott-Schottky (MS) diagram. Figure 3 As shown in (cd), the slopes of the MS curves of MIL-101(Cr) and TiO2 are both positive, indicating that both materials are n-type semiconductors. The Efb of MIL-101(Cr) and TiO2 relative to Hg / Hg2Cl2 are -1.0V and -0.90V, respectively. Considering that the flat band potential of an n-type semiconductor is usually 0.2V lower than the conduction band (CB) potential, the CB potentials of MIL-101(Cr) and TiO2 relative to the standard hydrogen electrode are -1.0V and -0.90V, respectively. Combined with the band gap (Eg), the corresponding valence band potentials (VB) of MIL-101(Cr) and TiO2 are 1.52V and 2.61V, respectively.

[0054] To further analyze whether MIL-101(Cr) and TiO2 form a heterojunction, X-ray electron spectroscopy and in-situ X-ray electron spectroscopy were performed. The full scan spectrum of MIL-101(Cr) clearly shows the characteristic peaks corresponding to C 1s, O 1s, and Cr2p, indicating that C, O, and Cr are the main elements of MIL-101(Cr), such as Figure 3 In addition to the characteristic peaks of C1s, O 1s, and Cr 2p, the full scan spectrum of 23% TiO2 / MIL101(Cr) also has the characteristic peak of Ti 2p, which further indicates that 23% TiO2 / MIL-101(Cr) contains TiO2.

[0055] In the high-resolution Ti 2p spectrum of TiO2, 458.56, 464.23, and 471.55 eV can be assigned to Ti2p 3 / 2, Ti2p 1 / 2, and Ti satellite peaks, e.g. Figure 6 (f). Compared with TiO2, the binding energy of these peaks in 23% TiO2 / MIL101(Cr) increased by 0.11 eV, indicating that electrons were transferred from titanium dioxide to MIL-101(Cr) after contact. In the high-resolution Cr 2p spectrum of MIL-101(Cr), the peaks at 577.46 and 587.06 eV were attributed to Cr 2p3 / 2 and Cr 2p 1 / 2, respectively. At the same time, the binding energy of Cr decreased by about 0.24 eV after contact with TiO2, further indicating that electrons were transferred from TiO2 to MIL-101(Cr) after contact. Therefore, an internal electric field (IEF) was formed between TiO2 and MIL-101(Cr), and the direction of this IEF was MIL-101(Cr). In situ XPS further demonstrated that electrons would be transferred from MIL-101(Cr) to TiO2 under light irradiation, indicating that TiO2 would be an active site for hydrogen production. Based on the band positions, XPS, and in situ XPS results, it can be safely concluded that a type II heterojunction is formed between MIL-101(Cr) and TiO2, and with the help of IEF, the electrons of MIL-101(Cr) on CB can be easily transferred to TiO2 for further hydrogen production. It should be noted that the newly formed structure satisfies both hydrogen reduction and TEOA oxidation potentials.

[0056] The photoelectric properties of the catalyst, such as the generation and separation of photogenerated carriers, were studied, and transient photocurrent, photoluminescence (PL) and EIS were performed.

[0057] The photoelectrochemical performance of the photocatalyst was evaluated using a CHI-750E electrochemical analyzer in a standard three-electrode system, with a carbon rod as the counter electrode, Hg / Hg2Cl2 as the reference electrode, carbon paper loaded with photocatalyst as the working electrode, and 1M KOH standard solution as the electrolyte solution. Working electrode preparation method: 2 mg of photocatalyst was added to a mixture of 1 mL of ethanol and 50 μL of Nafion, and ultrasonicated for 30 minutes to form a uniform mixed solution. 100 μL of the mixed solution was dropped five times on 1×1 cm carbon paper, and then fixed on the working electrode for testing the photoelectrochemical performance, including transient photocurrent, electrochemical impedance spectroscopy (EIS) and Mott-Schottky.

[0058] like Figure 6 As shown in (a) and 7, compared with the original MIL-101(Cr) and other x% TiO2 / MIL-101(Cr), 23% TiO2 / MIL-101(Cr) exhibits the strongest photocurrent response, indicating that the number of photogenerated carriers formed by 23% TiO2 / MIL-101(Cr) under illumination is the largest. Photoluminescence (PL) measurements further show that 23% TiO2 / MIL-101(Cr) has the weakest fluorescence intensity, indicating its best ability to separate photogenerated carriers, as shown in Figure 5. Figure 8 . EIS can well test the transport resistance of photogenerated carriers. The semicircle diameter of 23% TiO2 / MIL-101(Cr) is the smallest, indicating that it has the best charge transfer ability. In summary, 23% TiO2 / MIL-101(Cr) has the best photogenerated carrier generation, separation and transport capabilities, which is beneficial to the subsequent photocatalytic reaction. This result can be attributed to the Type II heterojunction formed by TiO2 and MIL-101(Cr), which inhibits the recombination of photogenerated electrons and holes and promotes their separation and transport.

[0059] The hydrogen production performance of the photocatalyst was evaluated using an online photocatalytic hydrogen production test device. The photocatalytic hydrogen production experiment was carried out in a 100mL airtight reactor. A 300W xenon lamp was used as a visible light source to conduct a photocatalytic cracking test of water for hydrogen production. 20mg of photocatalyst was dispersed in a mixed solution of 1.25mL triethanolamine (TEOA) and 22.75mL acetonitrile under the full spectrum. At the same time, the reaction system was vacuumed for 30 minutes to remove the air. Continuous stirring was maintained throughout the reaction to prevent catalyst agglomeration. The circulating cooling water was maintained at 6°C to ensure a constant temperature in the catalytic reaction system. Using argon as the carrier gas, a GC-7910 gas chromatograph-thermal conductivity detector (GC-TCD) was used to detect and record the H2 produced by the reaction online every 1 hour. Figure 6 As shown in (d), the hydrogen production of pure MIL-101(Cr) and pure TiO2 after 5 h is 130.69 μmol g-1 and 148.46 μmol g -1 The hydrogen evolution rate of x% TiO2 / MIL-101(Cr) increased significantly under the same conditions. With the increase of TiO2 content, the hydrogen evolution rate of x% TiO2 / MIL-101(Cr) first increased and then gradually decreased, among which 23% TiO2 / MIL-101(Cr) was the highest, with a hydrogen production of 884.01μmolg after 5h. -1 , the rate is 176.81 μmol g -1 h -1 Excessive loading of TiO2 nanoparticles on the surface may hinder the absorption of light by MIL-101(Cr), thus reducing the rate of H2 evolution. Cyclic stability experiments show that the amount of H2 produced by 23% TiO2 / MIL-101(Cr) remains essentially unchanged after 4 cycles. Figure 6 (f), indicating its good stability.

[0060] Therefore, the present invention adopts a method for preparing a TiO2 / MIL-101(Cr) photocatalyst of the above structure, and TiO2 has the advantages of good chemical stability, non-toxicity, low cost and easy availability. MIL-101(Cr) has the advantages of good thermal stability, chemical stability and high specific surface area. In this study, a series of TiO2 / MIL-101(Cr) Type II heterojunctions were prepared by in-situ growth of TiO2 nanoparticles in MIL-101(Cr) by hydrothermal method for photocatalytic hydrogen production. Among them, 23% TiO2 / MIL-101(Cr) has the best photocatalytic hydrogen production performance, which is 2.6 times that of pure phase MIL-101(Cr). Its excellent hydrogen production performance is attributed to the Type II heterostructure formed by TiO2 and MIL-101(Cr), which optimizes the electronic and band structure in the composite material, promotes the separation and transmission of photogenerated carriers, and thus improves the catalytic activity. A series of characterization methods such as XRD, SEM, infrared, Raman, and in-situ XPS prove the formation of Type II heterostructure. Solid-state UV, Tauc plot and Mott-Schottky plots prove that the heterostructure band structure thermodynamically satisfies the photocatalytic hydrogen production capability. Transient photocurrent, electrochemical impedance spectroscopy and fluorescence spectroscopy further show that 23% TiO2 / MIL-101(Cr) has the best photogenerated carrier separation capability and achieves efficient photocatalytic hydrogen production kinetically.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a TiO2 / MIL-101 (Cr) photocatalyst, characterized in that: The following steps are included: Step 1, synthesis of MIL-101(Cr): Terephthalic acid and chromium (III) nitrate nonahydrate were added to a reaction kettle, 14 mL of water and 0.1 mL of HF were added, and ultrasonication was performed for 20 min to obtain a uniform solution. The mixture was transferred into a polytetrafluoroethylene-lined reaction kettle for reaction. After the reaction was completed, the mixture was naturally cooled to room temperature, and the precipitate was collected by centrifugation and washed with DMF and ethanol several times, and dried in vacuum at 60°C to obtain MIL-101 (Cr); Step 2, synthesis of TiO2 precursor solution: Add concentrated nitric acid to ethanol and add tetrabutyl titanate, stir to prepare TiO2 precursor solution, and use it immediately after preparation; Step 3, preparation of x%-TiO2 / MIL-101(Cr): 30 mL of TiO2 precursor solution and 40 mg of MIL-101(Cr) were added to 20 mL of ethanol, and 0.3 mL of water was added. The mixture was stirred at room temperature for 30 min, and then the mixed solution was transferred to a high temperature and high pressure reactor for reaction. The solid obtained by centrifugation was washed three times with ethanol and then dried under vacuum conditions at 60°C to obtain a green powder, named x% TiO2 / MIL-101(Cr).

2. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 1, characterized in that: In the step 1, 0.333 g of terephthalic acid and 0.800 g of chromium (III) nitrate nonahydrate are used to prepare MIL-101 (Cr).

3. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 2, characterized in that: In the step 1, the reaction conditions in the polytetrafluoroethylene lined reactor are high temperature and high pressure at 220° C. for 8 hours.

4. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 3, characterized in that: In step 3, 140 μL of concentrated nitric acid is added to 120 mL of ethanol, and 200 μL of tetrabutyl titanate is added.

5. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 4, characterized in that: The mixing and stirring time in step 2 is 2 minutes, and the TiO2 precursor solution is prepared and used immediately.

6. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 5, characterized in that: The reaction condition of the high temperature and high pressure reactor in step 3 is heating at 120° C. for 24 hours.

7. The method for preparing a TiO2 / MIL-101(Cr) photocatalyst according to claim 6, characterized in that: The TiO2 / MIL-101(Cr) photocatalyst prepared by the above method is used to achieve efficient photocatalytic hydrogen production.

Citation Information

Cited By

  • Preparation method of bionic photosynthetic membrane and method for enhancing ion pump effect by light

    CN120399306A